Characteristic and applications of single polymer composites - Żenkiewicz, M.; Moraczewski, K.; Rytlewski, P.; Stepczyńska, M.; Żuk, T. (Polimery, 2015)
This paper constitutes a review of the literature concerning properties and applications of the single polymer composites (SPC). These materials are a relatively new and promising group of polymer composites which have good mechanical properties and high potential of application. The types and selected properties of single polymer composites were discussed. The most significant of these properties include adhesion at the interface of reinforcement and matrix, different melting points of crystalline phase of reinforcement and matrix, tensile strength and Young's modulus. Additionally, SPC currently produced in an industrial scale were characterized.